Self-Assembly and Cascade Catalysis by a Soft-Oxometalate (SOM) System - Das, Kousik; Yan, Tingting; Paul, Shounik; Qiu, Shilun; Ben, Teng; Roy, Soumyajit (Frontiers in Chemistry, 2020)
Cascade catalysis has gained importance due to its various applications. In this work we have performed cascade catalysis using a synergistically self-assembled soft-oxometalate (SOM) as a model system. At first we have synthesized an oxometalate (OM) hybrid with a polymerizable organic cation, namely tetrakis(4-aminophenyl)methane and a OM, K8[SiW11O39]. The hybrid in turn has been converted into SOM in water, DMSO mixture and characterized by different technics, ranging from electron microscopy to DLS. The SOM state is endowed with synergistic ability to polymerize the aniline based counter ions associated with it in presence of UV-light. Such polymerization is possible owing to the presence of photocatalytic OMs (oxometalates) in the SOMs. The polymer-SOM hybrid in cascade oxidizes selectively aniline to nitrobenzene and nitrite to nitrate owing to the residual oxidizing property of the OM constituents in it. This is the first example of cascade catalysis in SOM chemistry.